2006
DOI: 10.1073/pnas.0607073103
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity after repeated stimulation of residual spatial channels in blindsight

Abstract: Lesions of the occipital cortex result in areas of cortical blindness affecting the corresponding regions of the patient's visual field. The traditional view is that, aside from some spontaneous recovery in the first few months after the damage, when acute effects have subsided the areas of blindness are absolute and permanent. It has been found, however, that within such field defects some residual visual capacities may persist in the absence of acknowledged awareness by the subject (blindsight type 1) or imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
138
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(146 citation statements)
references
References 27 publications
6
138
0
2
Order By: Relevance
“…We have recently shown that subjects can be trained to perform on and to see stimuli that are initially invisible to them (9). We thus hypothesize that awareness is trainable, a conclusion that is in accordance with recent findings in blindsight patients (10). However, the time course of those learning effects has not been explored, i.e., whether the improvements in sensitivity and subjective awareness depend on each other.…”
supporting
confidence: 70%
“…We have recently shown that subjects can be trained to perform on and to see stimuli that are initially invisible to them (9). We thus hypothesize that awareness is trainable, a conclusion that is in accordance with recent findings in blindsight patients (10). However, the time course of those learning effects has not been explored, i.e., whether the improvements in sensitivity and subjective awareness depend on each other.…”
supporting
confidence: 70%
“…Previous research on a number of cases with blindness after brain injury shows that repeated exposure to first-order stimuli over a period, using an experimental paradigm similar to those reported here, can lift performance from chance to well-above-chance levels, but without awareness (type I blindsight). Further systematic exposure to first-order stimuli over extended periods of time can result in type II performance (19,20). It would be of interest to investigate whether transition from type I to type II would be less likely with repeated stimulation with second-order stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is now a growing body of evidence demonstrating that perceptual training can also increase the reported perceptual awareness of stimuli in blindsight patients (e.g. Sahraie et al, 2006). Also, studies in intact subjects exposed to subliminal presentation of visual stimuli (mostly utilizing the above-mentioned metacontrast masking in a "stimulus onset asynchrony" paradigm) have demonstrated that even in individuals without injury to the brain, training can increase the degree of perceptual awareness of a stimulus originally unavailable to consciousness (e.g.…”
Section: Implications Of the Ref-model For Posttraumatic Rehabilitatimentioning
confidence: 99%